Diffraction of γ-rays with energies of 1.17 and 1.33 MeV by a flat Si crystal. (16th April 2015) - Matsuba, Shunya; Hayakawa, Takehito; Shizuma, Toshiyuki; Nishimori, Nobuyuki; Nagai, Ryoji; Sawamura, Masaru; Angell, Christopher T.; Fujiwara, Mamoru; Hajima, Ryoichi
Abstract: Diffraction of γ-rays by a flat Si crystal has been demonstrated using a high flux 60 Co source with an intensity of 2.3 TBq. The diffraction intensities of the γ-rays with energies of 1.17 and 1.33 MeV have been measured as a function of the rotation angle of the crystal. Three peaks corresponding to the Si(440) and Si(220) diffractions for 1.17 MeV and the Si(440) diffraction for 1.33 MeV have been measured. The heights and shapes of these three peaks are well reproduced by taking into account Bragg's law and the experimental geometry.